A study of primitive religion - Cook, Jessie Leona (Travis) (My University, 1906)
Introduction: The original meaning of religion is that of “binding fast the human mind to a sense of the obligation which it owes to supernatural powers.” We find in the primitive history of all nations a religion, that is a conscious relation between man and some higher power and the manifestation of that relation in human conduct. The oldest religion of all nations is mythology which represents the earliest attempt of the mind to account for the mysteries of the world. For man in his most primitive stage had too create an understanding to enable him to attain at once to a clear and definite conception of a deity. He knew nothing about laws, nothing about physical forces, and nothing about the relation of cause to effect. In his total ignorance of cause he wondered at everything, and tried to get the meaning of life by what he could hear, see, and feel. He had developed no reasoning faculties and had not learned to observe and draw conclusions. He had only his fancies and beliefs and these often lead him far from the truth, for in primitive times there was no check upon fancy.
Citation: Cook, Jessie Leona (Travis). A study of primitive religion. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Religion; History; Theses; Manuscripts (documents)